Hierarchical Pore Structures: Correlative Laboratory Nano‐CT and 360° Electron Tomography of Macropore Structures in Hierarchical Zeolites (Adv. Mater. Interfaces 4/2021). Issue 4 (19th February 2021) - Apeleo Zubiri, Benjamin; Wirth, Janis; Drobek, Dominik; Englisch, Silvan; Przybilla, Thomas; Weissenberger, Tobias; Schwieger, Wilhelm; Spiecker, Erdmann
Abstract : Hierarchical pore structures exhibit features on several length scales governing important materials properties. Correlative 360° electron tomography and lab‐based Nano‐CT allowing for scale‐bridging 3D analyses of volumes of (60 μm) 3 with nm‐resolution were applied to macroporous zeolite particles. More details can be found in article number 2001154 by Benjamin Apeleo Zubiri, Erdmann Spiecker, and co‐workers.